2017
DOI: 10.1128/aac.00238-17
|View full text |Cite|
|
Sign up to set email alerts
|

Reduced-Concentration Clavulanate for Young Children with Acute Otitis Media

Abstract: Amoxicillin-clavulanate (A/C) is currently the most effective oral antimicrobial in treating children with acute otitis media (AOM), but the standard dosage of 90 mg amoxicillin/6.4 mg clavulanate/kg of body weight/day commonly causes diarrhea. We examined whether an A/C formulation containing lower concentrations of clavulanate would result in less diarrhea while maintaining plasma levels of amoxicillin and clavulanate adequate to eradicate middle-ear pathogens and to achieve clinical success. We conducted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
0
10
0
5
Order By: Relevance
“…In the majority of studies, subjects were admitted to the pediatric ( n = 9) or neonatal ward ( n = 4). One study was performed on the pediatric intensive care [ 24 ], in one study, patients received home-based treatment [ 25 ]. In the remaining three studies, the setting was unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of studies, subjects were admitted to the pediatric ( n = 9) or neonatal ward ( n = 4). One study was performed on the pediatric intensive care [ 24 ], in one study, patients received home-based treatment [ 25 ]. In the remaining three studies, the setting was unknown.…”
Section: Resultsmentioning
confidence: 99%
“…2.5 mg/kg 2. 5 mg/kg Oral Not with food Blood T = 15, 30, 45 min, 1, 2, 4, 8 h Hober-man et al [ 25 ] Amoxicillin/clavulanic acid (28:1) 1. 1.6 mg/kg 2.…”
Section: Resultsmentioning
confidence: 99%
“…These data may have implications regarding the clinical observation that amoxicillin/clavulanate therapy results in significantly increased incidence of antibiotic-associated diarrhea (AAD) compared to treatment with amoxicillin alone [18]. Clavulanate was assumed to be the causative agent as it increases intestinal motility in children [18], and amoxicillin/clavulanate formulations containing lower clavulanate ratios reduced AAD rates [18,25]. However, data from the current canine study revealed that amoxicillin/clavulanate causes more alterations in gut microbiota composition than amoxicillin alone, suggesting that microbiome damage is a mechanism responsible for AAD.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, several studies have recommended shorter courses for children, particularly for infants under two years of age, with 5-7 day courses being recommended. [42][43][44][45][46][47] The prescription of analgesics was shown to be practically routine, with 97.1% of doctors prescribing analgesics in addition to antibiotics for the management of otalgia and other symptoms. This concern with treating pain is in agreement with the AAP recommendations.…”
Section: Discussionmentioning
confidence: 99%